Characterisation of the maize leaf patterning mutants Wavy auricle in blade1-R and milkweed pod1-R : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Plant Biology at Massey University, Palmerston North, New Zealand - Johnston, Robyn Maree (Massey University, 2007)
The maize leaf has three main axes of growth, with an asymmetric distribution of tissue types along each axis. This study focuses on three mutants, Wavy auricle in blade1-R (Wab 1-R), liguleless1-R (lg1-R) and milkweed pod1-R (mwp1-R) that disrupt axial patterning of maize leaves. Dominant Wab1 mutations disrupt both medial-lateral and proximal-distal patterning. Wab1 leaf blades are narrow and ectopic auricle and sheath-like tissues extend into the leaf blade. Previous analyses have shown that Lg1 acts cell-autonomously to specify ligule and auricle tissues. The current study reveals additional roles in defining leaf shape. The recessive lg1-R mutation exacerbates the Wab1-R phenotype; in the double mutants, most of the proximal blade is deleted and sheath tissue extends along the residual blade. A mosaic analysis of Wab1-R was conducted in Lg1 and lg1-R backgrounds to determine if Wab1-R affects leaf development in a cell-autonomous manner. Normal tissue identity was restored in all wab1/- sectors in a lg1-R mutant background, and in three quarters of sectors in a Lg1 background. These results suggest that Lg1 can influence the autonomy of Wab1-R. In both genotypes, leaf-halves with wab1/- sectors were significantly wider than non-sectored leaf-halves, suggesting that Wab1-R acts cell-autonomously to affect lateral growth. mwp1-R is a recessive mutation that specifically affects patterning of sheath tissue. Characterisation of the mwp1-R phenotype revealed that mwp1-R husk leaves and the sheaths of vegetative leaves develop pairs of outgrowths on the abaxial surface associated with regions of adaxialised tissue. In situ hybridisation confirmed that disruptions to adaxial-abaxial patterning are correlated with misexpression of leaf polarity genes. Leaf margins and fused organs such as the prophyll are most severely affected by mwp1-R. The first two husk leaves normally fuse along adjacent margins to form the bi-keeled prophyll. In the most severe cases the mwp1-R prophyll is reduced to an unfused, two-pronged structure and keel outgrowth is significantly reduced. We speculate that the adaxial-abaxial patterning system has been co-opted during evolution to promote outgrowth of the keels in normal prophyll development. The results of this study place Mwp1, wab1 and Lg1 in a network of genes that regulate leaf polarity and axial patterning.
Keywords: Corn genetics; Maize leaf growth; Fields of Research::270000 Biological Sciences::270200 Genetics